FINANCIAL MARKETING AND ITS DEVELOPMENT PROSPECTS IN UKRAINE - KOVALCHUK, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
This article is devoted to the study of financial marketing and its development prospects in Ukraine. Financial marketing is an important tool for financial institutions, companies and organizations that helps to achieve success in a competitive market. The article examines the basic concepts and principles of financial marketing, such as market segmentation, target positioning, product development, and market promotion. The author analyzes the differences and disagreements between such concepts as: financial marketing and marketing of financial services. The author’s definition of financial marketing is provided as "the process of planning, implementation and control of marketing strategies and activities aimed at the formation, promotion and promotion of financial products and services, attracting new customers, increasing sales of financial assets and maintaining relations with existing customers in the financial sector". Special attention is paid to the analysis of prospects for the development of financial marketing in Ukraine. Current trends and challenges faced by financial institutions in Ukraine are considered. The importance of innovations and technologies in financial marketing is noted, as well as the impact of digitalization on the development of this field of activity. The author of the article predicts the future development of financial marketing in Ukraine and formulates recommendations for achieving competitive advantages by financial institutions under the conditions of applying marketing innovations. This article is based on current research and professional literary sources, and also takes into account the specifics of the development of the financial services market of Ukraine. It can be useful for specialists in the field of finance, marketing and strategic management, as well as for business leaders and managers who are interested in issues of the financial sphere in Ukraine.